Does Government subsidy for costs of medical and pharmaceutical services result in higher service utilization by older widowed women in Australia? - Tooth Leigh R; Hockey Richard; Treloar Susan; McClintock Christine; Dobson Annette (BMC, 2012)
Abstract Background In Australia, Medicare, the national health insurance system which includes the Medical Benefits Scheme (MBS) and Pharmaceutical Benefits Scheme (PBS), provides partial coverage for most medical services and pharmaceuticals. For war widows, the Department of Veterans' Affairs (DVA) covers almost the entire cost of their health care. The objective of this study was to test whether war widows have higher usage of medical services and pharmaceuticals. Methods Data were from 730 women aged 70-84 years (mostly World War II widows) participating in the Australian Longitudinal Study on Women's Health who consented to data linkage to Medicare Australia. The main outcome measures were PBS costs, claims, co-payments and scripts presented, and MBS total costs, claims and gap payments for medical services in 2005. Results There was no difference between the war widows and similarly aged widows in the Australian population without DVA support on use of medical services. While war widows had more pharmaceutical prescriptions filled they generated equivalent total costs, number of claims and co-payments for pharmaceuticals than widows without DVA support. Conclusions Older war widows are not using more medical services and pharmaceuticals than other older Australian women despite having financial incentives to do so.